Synthesis of ascorbyl oleate by transesterification of olive oil with ascorbic acid in polar organic media catalyzed by immobilized lipases - Moreno-Pérez, Sonia; Filice, Marco; Guisán, José Manuel; Fernández-Lorente, Gloria (Chemistry and Physics of Lipids, 2013)
The reaction of transesterification between oils (e.g., olive oil) and ascorbic acid in polar anhydrous media (e.g., tert-amyl alcohol) catalyzed by immobilized lipases for the preparation of natural liposoluble antioxidants (e.g., ascorbyl oleate) was studied. Three commercial lipases were tested: Candida antarctica B lipase (CALB), Thermomyces lanuginosus lipase (TLL) and Rhizomucor miehei lipase (RML). Each lipase was immobilized by three different protocols: hydrophobic adsorption, anionic exchange and multipoint covalent attachment. The highest synthetic yields were obtained with CALB adsorbed on hydrophobic supports (e.g., the commercial derivative Novozym 435). The rates and yields of the synthesis of ascorbyl oleate were higher when using the solvent dried with molecular sieves, at high temperatures (e.g. 45 °C) and with a small excess of oil (2 mol of oil per mol of ascorbic acid). The coating of CALB derivatives with polyethyleneimine (PEI) improved its catalytic behavior and allowed the achievement of yields of up to 80% of ascorbyl oleate in less than 24 h. CALB adsorbed on a hydrophobic support and coated with PEI was 2-fold more stable than a non-coated derivative and one hundred-fold more stable than the best TLL derivative. The best CALB derivative exhibited a half-life of 3 days at 75 °C in fully anhydrous media, and this derivative maintained full activity after 28 days at 45 °C in dried tert-amyl alcohol. This work was sponsored by the Spanish Ministry of Science and Innovation (project AGL-2009-07526) and Consolider INGENIO 2010 CSD2007-00063 FUN-C-FOOD (CICYT). Peer Reviewed